Implementation of the Action Research Cycle on Mental Training for Young Baseball Athletes - Hasanah, Uswatun; Juriana, Juriana; Deasyanti, Deasyanti; Wahyuni, Lussy Dwiutami (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The development of young athletes requires serious attention to mental aspects, including in baseball. They need to receive mental training from an early age to maintain their motivation to participate and practice sports. This study aims to determine the effectiveness of goal-setting training in increasing the motivation of young baseball players under the age of 16 who are trained by local governments. This method uses a three-cycle action research design to observe the gradual increase in athlete motivation to determine increase in athlete motivation. The instrument used is the Intrinsic Motivation Inventory (IMI) questionnaire (McAuley et al., 1989), which consists of four aspects, with the following reliability coefficients: interest-enjoyment (r=0.78); perceived competence (r=0.80); effort-importance (r=0.84); and tension-pressure (r=0.68). The results of the study in cycle I showed an increase in motivation from a score of 71.61 (86.28%) to 73.94 (89.09%). The results of cycle II showed an increase in motivation scores to 75.89 (91.43%), and the results of cycle III showed an increase in motivation scores to 76.22 (91.83%). Thus, it can be concluded that mental training interventions in the form of goal-setting exercises have succeeded in increasing the motivation of baseball athletes. More holistic mental training is needed to improve the mental skills of baseball athletes in the future.